Empaako, the Magic Word: A Special Form of Address Used in Western Uganda - Heusing, Gerald (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
This paper investigates Empaako, a special form of address and communicative process used in western Uganda. Through a historical and ethnographic background, the next section explores the linguistics of the magical word. Next, the paper traces naming and traditional names and examines examples of such naming for the Banyoro and Bantoro peoples. In particular, it discusses the etymologies for six semantic categories of secret names and how they have been reduced in these modern times to four groups. Meanwhile, more and more Batooro and Banyoro families are replacing traditional naming with a more European style of naming in which the clan’s name becomes the surname and a given name is derived from either Islam or Christianity. Finally, what remains is the requirement to employ Empaako communicatively to show respect and intimacy, and to avoid taboo violation.